Validity and Reliability of Editorial Plan Product Assessment Rubric in Digital Public Relations Course - Alfelia Nugky Permatasari (INVOTEC, 2022)
This study aims to determine the validity and to estimate the reliability of the editorial plan product assessment rubric in the Digital Public Relations course. The focus of the research is the content validity and reliability estimation of the product assessment rubric: editorial plan. The Content Validity Ratio (CVR) and Content Validity Index (CVI) from the assessment rubric and V Aiken were calculated using Ms. Excel. The Calculation of content validity by five experts was valid. The Interclass Correlation Coefficients (ICC) were used to estimate the reliability of the scoring rubric and were calculated using SPSS 24.0 software. The rubric was tested on 3 raters who assessed 30 students each. The results of the calculation of the reliability estimate show a good level of reliability. This validity and reliability estimation of the rubric is expected to be able to support an objective assessment, especially on editorial planning products in the Digital Public Relations course.